Orientation of the Cleavage Map of the 200-Kilodalton Polypeptide Encoded by the Bottom-Component RNA of Cowpea Mosaic Virus - Goldbach, Rob (1983)
The genomic organization of the bottom-component RNA of cowpea mosaic virus was studied. In vivo, this RNA encodes at least eight different polypeptides of 170, 110, 87, 84, 60, 58, 32, and 4 kilodaltons (K), the last polypeptide representing the genome-bound protein VPg. In rabbit reticulocyte lysates, bottom-component RNA is translated into a 200K polypeptide which is then processed to give the 32 and 170K polypeptides also found in vivo. By pulse-labeling the 200K primary translation product, we now show that the 32 and 170K polypeptides are derived from the NH(2)-terminal and COOH-terminal parts of this polypeptide, respectively. Comparison of the proteolytic peptide patterns of 170K polypeptides synthesized in vitro and pulse-labeled at either the NH(2)-terminal or the COOH-terminal end with the patterns of the 170 and 110K polypeptides found in vivo demonstrates that the order within the 200K primary translation product of cowpea mosaic virus bottom-component RNA is as follows: NH(2)-32K polypeptide-58K polypeptide-VPg-24K polypeptide-87K polypeptide-COOH.